Shopping on Social Planet: The Mediating Role of Trust - Wan Rasyidah Wan Nawang; Intan Fatimah Anwar; Amalina Mursidi; Najwa Mohd Najibd; Raja Azhan Raja Mamat (University of Zagreb, Faculty of Economics and Business, Marketing Department, and CROMAR (Croatian Marketing Association), 2025)
Indexed by WOS/Scopus/ERA